2017
DOI: 10.1103/physrevb.96.184102
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of supercooled liquid antimony: A density functional study

Abstract: Crystallization of liquid antimony has been studied at 600 K using six density functional/molecular dynamics simulations with up to 882 atoms and three scenarios: one completely disordered sample that did not crystallize even after 570 ps, four with fixed crystalline slab templates, and one with a fixed crystalline seed. Crystallization proceeded layer-by-layer in most cases and was rapid (∼36 m/s) with templates and somewhat slower with the seed. The seed simulation shows an unusual percolation asymmetry wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…DFT molecular dynamics simulations have shown indeed that Sb crystallizes very fast in the presence of a crystalline Sb boundary with growth velocity of about 36 m s −1 at 600 K while no sign of crystal nucleation was detected on the time scale of half a ns at the same temperature. 41 In fact, crystal nucleation does occur on the time span of a DFT-MD run, but only in the temperature range 300-500 K as reported in ref. 42 and 43. In agreement with previous DFT results, [41][42][43][44] homogeneous crystal nucleation in the supercooled liquid was not observed in NN-MD simulation on a ns time scale above 600 K. Supercritical nuclei appear instead on the time scale of 1-15 ns in the temperature range 300-450 K, but not below 300 K, as we discuss in more details later on.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…DFT molecular dynamics simulations have shown indeed that Sb crystallizes very fast in the presence of a crystalline Sb boundary with growth velocity of about 36 m s −1 at 600 K while no sign of crystal nucleation was detected on the time scale of half a ns at the same temperature. 41 In fact, crystal nucleation does occur on the time span of a DFT-MD run, but only in the temperature range 300-500 K as reported in ref. 42 and 43. In agreement with previous DFT results, [41][42][43][44] homogeneous crystal nucleation in the supercooled liquid was not observed in NN-MD simulation on a ns time scale above 600 K. Supercritical nuclei appear instead on the time scale of 1-15 ns in the temperature range 300-450 K, but not below 300 K, as we discuss in more details later on.…”
Section: Resultsmentioning
confidence: 77%
“…41 In fact, crystal nucleation does occur on the time span of a DFT-MD run, but only in the temperature range 300-500 K as reported in ref. 42 and 43. In agreement with previous DFT results, [41][42][43][44] homogeneous crystal nucleation in the supercooled liquid was not observed in NN-MD simulation on a ns time scale above 600 K. Supercritical nuclei appear instead on the time scale of 1-15 ns in the temperature range 300-450 K, but not below 300 K, as we discuss in more details later on. Therefore, in order to explore the crystallization speed in a wide temperature range, we consistently studied the crystal growth at a preformed crystal/amorphous interface which is also believed to be close to the experimental situation realized in the device of ref.…”
Section: Resultsmentioning
confidence: 77%
“…The (average) mean‐square displacement (msd) is in the context of PCMs particularly used in ab‐initio molecular dynamics (AIMD) simulations to derive atomic mobilities, which then via the Stokes‐Einstein relation can be related to viscosities. [ 169–171 ] So, there must be a kind of relation between the msd used in PCM research and the msd introduced in Equation . However, we have to be careful mixing msd acting on different length and time scales.…”
Section: Phase‐change Materials In Nanoscale Dimensionsmentioning
confidence: 99%
“…Here, information on the kinetics of pure Sb could not be obtained due to its extreme tendency to crystallize. Ab initio molecular dynamics (AIMD) simulations based on density functional theory (DFT) have shown that pure Sb can crystallize very rapidly in the presence of crystalline Sb boundaries, with an extremely high growth velocity of ≈36 m s −1 at T = 600 K . Such a crystallization speed is much greater than that of Ge 2 Sb 2 Te 5 .…”
Section: The Local Structural Motifs In Amorphous Sb In15sb85 and Gmentioning
confidence: 99%